Optimisation in open pit mining - Phillips, Raymond (My University, 2018)
The mining industry forms an integral part of South Africa - its society, culture, history and of course, its economy. This research dissertation focuses on the Open Pit Mine Production Scheduling Problem, a cornerstone in the design and planning of an open pit mining venture and its pro tability thereafter. The accompanying optimisation problem is usually both complex and large. We investigate existing initial solutions as well as two existing metaheuristic algorithms that have been used to solve this problem, improving upon them and introducing a pseudo greedy approach that seeks production schedule improvement in the immediate solution space neighbourhood. This addition greatly improves initial solutions to the problem. Through analysis on a smaller and larger mining instance we reveal the perceived advantages and disadvantages of two existing metaheuristics in producing optimal production schedules. We then propose a parent algorithm that interchangeably selects either of these algorithms based on probabilities determined by their observed performances during computation periods. The parent algorithm produces a strong production schedule that surpasses the current best found solution for the larger mining instance. With these ndings we propose a probabilistic selection method parent algorithm that interchanges between both algorithms in an e ort to achieve a better solution.
A dissertation submitted in ful lment of the requirements for the degree of Masters of Science in the School of Computational and Applied Mathematics , University of the Witwatersrand, Johannesburg, July 2018
Keywords: Strip mining; Strip mining--Environmental aspects